EXPLORING ANALGESIC EFFICACY OF DEXMEDETOMIDINE AND CLONIDINE AS ADJUVANTS IN CAUDAL EPIDURAL BLOCK WITH 0.2% ROPIVACAINE FOR PEDIATRIC LOWER ABDOMINAL SURGERIES - MANOJ KUMAR GUPTA; SANJAYA KUMAR GUPTA; VIKRAM SINGH RATHORE; DIVYA CHANDRA (Asian Journal of Pharmaceutical and Clinical Research, 2025)
Objectives: Effective post-operative pain management is crucial in pediatric anesthesia. Challenges such as distinguishing pain from hunger or fear in younger children and concerns about respiratory depression with opioid use have often resulted in inadequate pain control in this ppulation. Recent studies have highlighted the importance of addressing pediatric pain with the same seriousness as in adults, as pain in children can lead to similar physiological and psychological consequences. This prospective, randomized study aimed to compare the efficacy and safety of caudal ropivacaine with dexmedetomidine versus clonidine for post-operative analgesia in pediatric patients undergoing lower abdominal surgeries. In addition, we evaluated hemodynamic and respiratory changes in both treatment groups and monitored for any complications. Methods: A comparative prospective study was conducted involving 100 American Society of Anaesthesiologists status I or II male patients aged 2–8 years undergoing lower abdominal surgeries from January 2012 to December 2013. Patients were randomly assigned to two groups and received caudal epidural analgesia following general anesthesia induction. Group A received 0.2% ropivacaine (1 mL/kg) plus clonidine 1 μg/kg, while Group B received 0.2% ropivacaine (1 mL/kg) plus dexmedetomidine 1 μg/kg. Intraoperative monitoring included heart rate (HR), mean arterial pressure (MAP), oxygen saturation, electrocardiogram, and end-tidal carbon dioxide levels. Post-operative sedation scores and Visual Analog Scale scores for pain relief were recorded. Results: Statistical analysis using the Statistical Package for the Social Sciences release 12.0 showed a significant increase in HR and MAP at intubation, which declined after caudal block. There was a decrease in HR and MAP from baseline to minimum, but no intervention was required. Both groups exhibited similar post-operative sedation levels, with a significant increase in duration of post-operative analgesia in Group B. Conclusion: In conclusion, as a caudal adjuvant to 0.2% ropivacaine, dexmedetomidine at a dosage of 1 μg/kg provided significantly longer post-operative analgesia and improved hemodynamic stability compared to clonidine 1μg/kg, without excessive sedation or major side effects.